Impact of the COVID-19 pandemic on adherence to infection prevention and control measures between 2019 and 2021 in Swiss sentinel private practices: repeated cross-sectional surveys (Swiss Medical Weekly, 2022)
AIMS OF THE STUDY: The COVID-19 pandemic has shown the importance of infection prevention and control (IPC) measures in health care settings, including primary care. We aimed to describe how it influenced adherence to infection prevention and control measures in private practices in the Swiss sentinel network (Sentinella).METHOD: An online cross-sectional survey was sent to the 181 Sentinella practices in 2021 that included questions on the practice’s spatial organisation, staff habits and vaccination coverage, ventilation, mask wearing, hand hygiene, as well as triage and separation of patients with suspected infection. Results were compared with those of a 2019 survey conducted in the same setting.RESULTS: We received 127 valid questionnaires (70.2% response rate). At the time of the study, SARS-CoV-2 vaccination was underway among physicians (51.3%). Between 2019 and 2021, an absence of specific recommendations on mask wearing for staff (55.7%) changed into a recommendation for continuous wearing (93.7%); hand hygiene improved, especially upon arrival at the practice (63.9% vs 85.8%; p